Development of module based introduction, connection, application, reflection, extention (icare) on ion balance and pH of salt solution class xi sma/ma - R. Usman Rery; Sri Haryati; Intan Shanderi (Pascasarjana Universitas Negeri Medan, 2022)
The development of a ICARE-based Module on the material of ion balance and pH of salt solution aims to develop a valid module and determine user responses in learning. The research method used is the research and development (R&D) method by applying a 4-D development model which includes Define, Design, Develop and Disseminate, pandemic conditions cause research to only be carried out until the Develop stage which was followed by one-on-one trials, teacher trials, and limited trials. The data collection tools used are validity sheets and user response questionnaires. The data analysis technique used is to calculate the results of the validation percentage score and user response. The results of the study explain that the ICARE-module developed has been categorized as